Transporte de carbono orgânico dissolvido no estuário do Rio Jaguaribe sob clima semiárido - Cavalcante, Mariany Sousa (2015)
Estuaries are pathway for dissolved organic carbon (DOC) from the coastal to the sea. However, before reaching the ocean, DOC can suffers biogeochemical transformations and influence of estuarine hydrodynamics, which responds to seasonal, and tidal changes. This study analyzed the spatial and temporal variability of DOC, the hydrochemical and physical aspects of Jaguaribe river estuary, under different climate conditions (dry and rainy) and tide (ebb / flood). The spatial variation of the DOC was between 1.1 and 6.4 mg L-1 in the dry season and between 1.1 and 9.15 mg L-1 in the rainy season. There was no great seasonal variability in DOC concentrations, probably due to low levels of rainfall in wet seasons. The hydrogeochemical DOC behavior was different between the seasons. In the dry season, the DOC showed conservative behavior, highly influenced by physical processes because the tidal effects were dominants in the estuary in this season . In the rainy season, the DOC presented non-conservative behavior, linked to biological activity. The DOC was strongly correlated with the residence time and the amount of freshwater, it shows the importance of fluvial descharge to the estuarine DOC input. The values of DOC, freshwater input and residence time increased toward the coastal, indicating retention of freshwater and DOC upstream. The mixing zone of the Jaguaribe River estuary behaved as a DOC retainer in the dry season and as an exporter in the rainy season. The COD flow was lower than expected for areas under semi-arid climate, possibly by rainfall was lower than the historical average.